Phycomyces: MODIFICATION OF LIGHT-INDUCED SPIRAL GROWTH AFTER MECHANICAL CONDITIONING OF THE CELL WALL - Gamow, R. Igor (1980)
Mature stage IVb Phycomyces sporangiophores show left-hand spiral growth; that is, viewed from above, the sporangium rotates clockwise. It has been shown that mechanical conditioning (strain-hardening) of the cell wall by the Instron technique increases the ratio of rotation to the elongation growth rate compared to nonmechanically conditioned controls. It is reported that the addition of a saturating light stimulus to these sporangiophores causes a decrease in the ratio of rotation to elongation growth rate. This result is in agreement with the fibril slippage model, i.e. the counterclockwise rotation of stage IVa is a result of parallel fibrils lying in a right-handed spiral configuration slipping by one another. It is suggested that a light stimulus added to a mechanically conditioned stage IVb sporangiophore activates one or more cell wall-loosening enzymes which act by decreasing the number of intermolecular bonds between parallel fibrils causing fibril slippage, resulting in counterclockwise rotation. It is precisely this counterclockwise contribution that decreases the rotation to elongation growth ratio of mechanically conditioned and then light-stimulated stage IVb sporangiophores.